IMPLEMENTASI PICTURE AND PICTURE UNTUK MENINGKATKAN KETERAMPILAN MENULIS DALAM PEMBELAJARAN BAHASA INGGRIS - suherni (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2019)
Writing is part of the language skills used to communicate and is considered to be one of the easiest aspects so that errors in descriptive writing are often found. This happens because descriptive writing requires an object that can be described because it requires a learning media that can help these problems. As for the problem of this research is whether through the Picture and Picture model can improve learning outcomes English aspects of writing descriptive texts in class VIII SMPN 2 Peureulak Barat. The purpose of the study was to improve the learning outcomes of English in the aspect of writing descriptive texts through the Picture and Picture model in class VIII of Peureulak Barat Middle School 2. This study uses descriptive analysis techniques. The sample of the eighth grade students of Peureulak West Junior High School 2 research was 20 students. Data collection techniques in this study are Student Worksheets and observation sheets. learning outcomes in cycle 1 are still unsatisfactory from 20 students, who completed only 12 students (60%) while the average score was only 67 and in cycle II 18 of the 20 students had completed their learning outcomes (90%) with an average score Student test scores reach 82.25. The results of this study indicate the application of the Picture and Picture Model can improve the learning outcomes of English aspects of descriptive text writing in Class VIII students of SMP Negeri 2 Peureulak Barat.